2023
DOI: 10.1007/s40474-023-00274-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Early Intervention Systems

Abstract: Purpose of Review Early intervention programs have been shown to increase the overall socio-emotional and physical wellbeing of children in early childhood and educational settings. The goal of this narrative review is to explore recent literature that describes implementation of these systems and highlights innovative practices in the early childhood intervention sector. Recent Findings Twenty-three articles were included, and we identified three themes in this review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…One of the studies failed to find any significant effect on development after the intervention. However, reviews on EI have always found a positive effect in programmes that intervene at home and with parents (Puthussery et al, 2018;Tollan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies failed to find any significant effect on development after the intervention. However, reviews on EI have always found a positive effect in programmes that intervene at home and with parents (Puthussery et al, 2018;Tollan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, EI programmes are based on theoretical foundations that highlight the importance of the context/environment and their relationship with the child (Tollan et al, 2023). Basically, six approaches can be identified: (1) the biopsychosocial model, developed by the World Health Organization (WHO, 2001), which seeks to integrate the child into his/her context as well as his/her autonomy; (2) the ecological-systemic model, which also seeks to normalise a child's situation and his/her continuing integration into his/her family and social context (Burger, 2014); (3) the transactional model, which also emphasises the interdependence of the child with his/her social context (Sameroff & Fiese, 2000); (4) Feuerstein's theory of structural cognitive modifiability (SCM) (Feuerstein & Jensen, 1980), focusing on a child's capacity for learning and maturation always within the mechanism of cultural transmission; (5) the activity-based approach (Bricker & Cripe, 1992), which proposes a global learning theory of the authors about developmental psychology and functional activities for a child's life; and (6) intervention programmes with a behavioural approach (Howlin et al, 2009), which are usually part of many of the elements of the previous programmes, but which have demonstrated their efficacy in a specific way, such as Applied Behaviour Analysis (ABA), Early Intensive Behaviour Intervention (EIBI), Treatment and Education of Children with Autism and Associated Communication Problems (TEACCH), the DENVER model , which involves intensive communication training, cognitive-behavioural therapy, and parent training, or the LOVAAS programme, which proposes a comprehensive and highly-structured training of functional and life-relevant behaviours for the child.…”
Section: Palabras Clavementioning
confidence: 99%
“…A review on early intervention systems has addressed innovative techniques in childhood disability interventions, policy practices, and trauma-informed care, emphasizing the importance of trauma-informed approaches in education and intervention for children and families facing social marginalization (Tollan et al, 2023). This review underscores the need for innovative and inclusive approaches to early intervention systems to address the diverse needs of children and families impacted by trauma.…”
Section: The Digital Adaptions and Innovative Interventions For Early...mentioning
confidence: 99%